The Relationship of the Test for Respiratory and Asthma Control in Kids Initial Score on the Prognosis of Pre-school Children With Asthma: A Prospective Cohort Study - Liu, Lu; Zhang, Jing; Zhang, Lei; Yuan, Shu-Hua; Wu, Jin-Hong; Tang, Ming-Yu; Chen, Jian-De; Zhang, Fen; Qi, Xin-Yi; Yin, Yong (Frontiers in Pediatrics, 2021)
Objective: The test for respiratory and asthma control in kids (TRACK) is currently the only standard follow-up tool for children under 5 years of age with asthma. The purpose of this study was to investigate the relationship between the TRACK initial score (Ti) and their prognosis after 6 months of follow-up in preschoolers with asthma. Design: a prospective cohort study. Methods: The study included preschoolers diagnosed with asthma at the Shanghai Children's Medical Center between January 2019 and June 2020, and follow-up for 6 months. TRACK scores, frequency of wheezing and respiratory infections, number of Emergency Department (ED) visits and treatment regimen were collected. According to the TRACK initial score, the children were divided into "Ti<60 group" and "Ti≥60 group", and the two groups were compared in terms of TRACK score related indicators, clinical manifestations and treatment. Results: There are 102 preschoolers included in the analysis (78 boys [76.5%] and 24 girls [23.5%]; mean [SD] age, 28.05 [11.63] months). After 6 months of follow-up, the TRACK score was improved in both groups, and the "Ti≥60 group" had a higher score, lower rate of uncontrolled asthma and fewer reassessments were required. There was no difference in the number of wheezing attacks between the two groups in terms of clinical presentation, but the "Ti < 60 group" had more respiratory infections and ED visits. Regarding the use of ICSs, in the "Ti < 60 groups”, the dose of ICSs was higher and reduced slowly, and the dose difference between the two groups began to appear after 5 months of follow-up. Conclusion: TRACK is essential for preschoolers with asthma at the time they are diagnosed. In addition, if the TRACK initial score is less than 60, the probability of poor prognosis is higher.